Treatment with Methylphenidate Improves Affective but Not Cognitive Empathy in Youths with Attention-Deficit/Hyperactivity Disorder - Pamela Fantozzi; Pietro Muratori; Maria Celeste Caponi; Valentina Levantini; Cristina Nardoni; Chiara Pfanner; Federica Ricci; Gianluca Sesso; Annalisa Tacchi; Annarita Milone; Gabriele Masi (MDPI AG, 2021)
Background: Beside the core symptoms, patients with attention-deficit/hyperactivity disorder (ADHD) frequently show relevant difficulty in developing relationships with peers. Although ADHD symptoms may account for social impairment, deficits in cognitive and/or affective empathy have also been involved. Our aim was to investigate the effect of methylphenidate (MPH) treatment on affective and cognitive empathy. Methods: Sixty-one drug-naïve youths with ADHD (age range 6 to 17 years, mean 10.3 ± 2.8 years, 51 males) naturalistically treated with MPH monotherapy were followed up for 6 months for ADHD symptoms and empathy, measured with the Basic Empathy Scale. Results: After being treated with MPH, the patients showed a significant improvement in affective and cognitive empathy scores. Linear regression models showed that changes in inattention symptoms predicted changes in affective but not in cognitive empathy, while changes in the hyperactivity/impulsivity symptoms did not predict changes in affective or cognitive empathy. Conclusions: Our study provides a further contribution for a better understanding of the possible effects of the MPH on youth's characteristics.